Knockdown Resistance (kdr) Mutations I1532T and F1534S Were Identified in Aedes albopictus Field Populations in Zhejiang Province, Central China - Wu, Yuyan; Liu, Qinmei; Qi, Yunpeng; Wu, Yinping; Ni, Qinxiang; Chen, Weihua; Wang, Jinna; Li, Tianqi; Luo, Mingyu; Hou, Juan; Gong, Zhenyu; Sun, Jimin (Frontiers in Cellular and Infection Microbiology, 2021)
Abstract Aedes albopictus is the only vector that can transmit the dengue virus in Zhejiang Province, central China, and it can develop insecticide resistance due to long-term exposure to pyrethroids. The presence of knockdown resistance (kdr) mutations is one of the mechanisms responsible for pyrethroid resistance, and has been reported in some Ae. albopictus populations in southern China. However, little is known about the DNA diversity of the voltage-gated sodium channel (VGSC) gene in Ae. albopictus populations in central China. Four Ae. albopictus field populations were collected, in Yiwu (YW), Quzhou (QZ), Wenzhou (WZ), and Jiaxing (JX) from Zhejiang Province, central China. The susceptibility of Ae. albopictus adults to three pyrethroids (beta-cypermethrin, deltamethrin, and permethrin) was tested using the WHO tube assay, and Kdr mutations were identified via PCR and sequencing. The relationship between kdr mutations and pyrethroid phenotypes was also analysed. Of the four populations, none was sensitive to any pyrethroid tested, and the YW population showed the strongest pyrethroid resistance. Non-synonymous kdr mutations were detected in codons 1532 and 1534, domain III. At codon 1534, one mutant allele, TCC(S), was detected in the four populations with a frequency of 42.08%, while at codon 1532, one mutant allele, ACC(T), was detected in the JX and QZ populations, with frequencies of 4.22% and 3.03%, respectively. The F1534S mutant allele was positively correlated with both beta-cypermethrin and deltamethrin resistance phenotypes (OR > 1, P < 0.05), whereas the I1532T mutant allele was possibly negatively correlated with beta-cypermethrin, deltamethrin, and permethrin resistance phenotypes (OR < 1, P > 0.05). In conclusion, resistance and resistance mutations regarding to three pyrethroids are already present in the Ae. Albopictus populations from Zhejiang, central China, which prompting the need to use non-insecticide-based methods of insect control.